The distribution, fall migration routes and survival of Ross's Geese - Melinchuk, Ross; Ryder, John P (Wildfowl, 1980)
Analysis of band recoveries indicates that approximately 90% of the harvest of central Arctic Ross's Geese Anser rossii occurs in Alberta, Saskatchewan and California with the latter state accounting for approximately 58% of the North American kill. Most of the population follow the traditional migration route to the Central Valley of California. Small numbers winter in Mexico and the Gulf coast area of Texas and Louisiana. Movement directly from the central Arctic to areas around Hudson Bay, as well as association on sympatric wintering grounds explains the expansion of Ross's Geese into the eastern Arctic. Survival rates of adult male and female and young male and female are approximately 86%, 82%, 48% and 46%, respectively. Immatures are 1.62 times more vulnerable to hunting mortality than adults.